What does education mean for us and how do we get involved? Parents’ accounts in a Mexican rural community - Azaola, Marta Cristina (International Journal about Parents in Education, 2007)
This research focuses on parental involvement in their childrens education in a mexican ruralcommunity. Drawing on bourdieus theory of social and cultural reproduction, the key conceptsunder investigation were field, habitus, social, cultural and symbolic capital. From an ethnographicperspective, data were collected through a variety of research methods in the autumn of 2005. I managed to interact closely with participants in order to investigate their attitudes, knowledge andpractices with respect to the formal and informal education in their own and their childrens lives. The values they transmitted to their children were also important objects of study. Investigatingparents background and their interaction with the community school was crucial in order tounderstand their constraints in getting involved in their childrens education. The paper analysesparents satisfaction with the provision of formal education in their community and, familieslimitations in getting involved. It also illustrates that parental involvement was regarded mainly as amothers task. The relevance of this study relies on the attempt to test bourdieus theory in an areathat has been generally under-explored as is the case of parental involvement in rural settings.